KEWENANGAN DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK PADA EDUKASI PELECEHAN SEKSUAL DI KOTA BITUNG - TESALONIKA, VABELLA.; TULUSAN, FEMMY; MAMBO, RULLY (Sam Ratulangi University, 2021)
Sexual violence is a serious problem facing modern civilization today, because acts of sexual violence showa malfunctioning of a norm in a person which results in the prohibition of human rights and the interests ofothers who are victims. In order to avoid sexual harassment, a person needs to be equipped with knowledgeor education about sexual harassment. Authority which usually consists of several powers, namely powerover a certain group of people or power over an area of government. One of the ways to prevent sexualviolence can be done by providing information and education, with this the Office of Women's Empowermentand Child Protection can exercise its authority by conducting socialization to local communities andeducating about the prevention and handling of violence. When the supervision occurs, the community canalso carry out supervision by assessing the workings and arrangements that are carried out so that clearcoordination and appropriate information can occur. This education is very much needed as a guide foreveryone to equip themselves to be able to understand about sexual harassment. The authority of the Officeof Women's Empowerment and Child Protection can be said to run well if it has provided education byobserving applicable regulations, coordinating (administration) with the community, and providingsupervision in the running of this program.Keywords: Authority, Education, Sexual Harassment